THINGS MAY NOT ALWAYS BE AS THEY SEEM - Ismail, Idazureen Ismas (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Atypical diabetes and late-onset Type 1 Diabetes Mellitus are rare, affecting only 10% of patients with diabetes. Presence of diabetes-associated autoantibodies such as Anti-Islet Cell (ICA), Anti-Glutamic Acid Decarboxylase (GAD), Anti-Insulinoma Associated Antigen-2 (IA2) and Zinc Transporter 8 (ZnT8) point towards type 1 over type 2 diabetes mellitus. CASE 1 A 55-year-old male with underlying autoimmune hypothyroidism and vitiligo was admitted for diabetic ketoacidosis (DKA) with the following laboratory findings: HbA1c 16.6%, random blood sugar (RBS) 43 mmol/L, serum ketone 6.7 mmol/L, pH 7.06 HCO3 5.1. He was lean with a body mass index (BMI) of 21 kg/m2 and no family history of diabetes. He was discharged well with metformin, dipeptidyl peptidase-4 inhibitor (DPP-4i) and basal insulin. Follow-up after two weeks showed erratic glucose control. Results showed positive ICA: 224 IU/ml (>28 IU/ml) and GAD: >280 IU/ml (>17 IU/ml) but negative IA2: 3.611 (<28 IU/ml) and low C-peptide 146 pmol/L (<367 pmol/L). He was diagnosed with latent autoimmune diabetes of adults (LADA), with differentials being late-onset Type 1 Diabetes Mellitus and autoimmune polyglandular syndrome. Treatment was revised to basal-bolus insulin. HbA1c improved to 11.6% within one year. CASE 2 A 33-year-old female, obese (BMI 28 kg/m2 ), with features of insulin resistance and diabetic parents, was admitted for DKA. – Laboratory results were as follows: RBS 31 mmol/L, serum ketone 5.3 mmol/L, pH 7.23, HCO3 14. Baseline HbA1c was 17.1%. She was started on subcutaneous insulin isophane) 34 units, T, Metformin XR 2 g ON and T and Vildagliptin 50 mg BD (DPP-4i) and was discharged with these medications. Self-monitoring blood glucose after two weeks was unsatisfactory. Results revealed normal C-peptide of 470 pmol/L (367-1467 pmol/L), negative IA2: <2.5 IU/ml (<28 IU/ml), positive ICA: 157IU/ml (>28 IU/ ml) and GAD: >280 IU/ml (>17 IU/ml). Maturity-onset diabetes of the young (MODY) was considered. Adding sulfonylureas resulted in suboptimal glycaemic control. HbA1c improved to 14.6% within one year after switching to premixed insulin. CONCLUSION Subclassifying diabetic patients with positive diabetesassociated autoantibodies necessitates a comprehensive approach, considering family history, phenotype and targeted genetic testing.